1988
DOI: 10.1093/ajcp/90.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Positive Direct Antiglobulin Test and High Serum Immunoglobulin G Values

Abstract: To investigate the association between the positive direct antiglobulin test (DAT) and hypergammaglobulinemia, the authors prospectively studied 154 patients, classified into three groups: Group 1, 52 patients with a positive DAT result in pretransfusion samples; Group 2, 52 patients with a negative DAT result; and Group 3, 50 patients initially found to have an elevated serum immunoglobulin G (IgG) level. Serum protein electrophoreses and IgG quantifications were performed for all three groups. Serum haptoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Only 0.6% of the 160 total elution studies performed at the adult hospital yielded new serologic information not available through the IAT. This finding is consistent with results reported previously, [1][2][3][4][5] although it is important to note that these studies used more stringent criteria, similar to those used at the pediatric hospital. However, by using the strict criteria presented in this study, we found that only 2.3% of the eluates yielded new serologic information (pediatric hospital).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only 0.6% of the 160 total elution studies performed at the adult hospital yielded new serologic information not available through the IAT. This finding is consistent with results reported previously, [1][2][3][4][5] although it is important to note that these studies used more stringent criteria, similar to those used at the pediatric hospital. However, by using the strict criteria presented in this study, we found that only 2.3% of the eluates yielded new serologic information (pediatric hospital).…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, the yield of elution tests contributing novel serologic information is thought to be low. [1][2][3][4][5] The criteria for performing elution testing vary across institutions and could affect the yield of the test to some extent. The primary indication for elution testing is a newly reactive DAT in the context of recent RBC transfusion (eg, 1 month).…”
mentioning
confidence: 99%
“…Several previous studies described a very low incidence of detecting a novel antibody in the eluate when it was not detectable in the serum. In these studies the eluate was informative for an antibody not identifiable by the routine pretransfusion testing of the serum in less than 1% of all eluates performed 2,4‐6 . In one of these reports, the lone antibody detectable only in the eluate, anti‐C w , was only detected in the eluate because a C w ‐positive cell was only present in the eluate antibody identification panel 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of an elevated cancer risk among DAT+ donors is uncertain. However, hypergammaglobulinemia is a common cause of DAT+, 1,7,10 and patients with polyclonal gammopathy or monoclonal gammopathy are at increased risk for cancer: After a median follow‐up of 67 months for patients with polyclonal gammopathy, hematologic disorders developed in 5 percent and nonhematologic malignancies in 3 percent in a study from the Mayo Clinic 13 . Another possible explanation for increased risk of lymphoproliferative disorders in donors with positive DATs may be the effect of chronic antigenic stimulation on the immune system, leading to the eventual development of a clonal B‐cell disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated serum immunoglobulin G (IgG) levels and nonreactive eluates have been found in 33 percent of patients with a positive DAT. The higher the elevated serum IgG, the more frequently a DAT+ result is observed 5,7 . An increased prevalence of gammopathies is found in lymphoma, hairy cell leukemia, gastric cancer, ovarian cancer, lung cancer, chondrosarcoma, and hepatocellular carcinoma, as well as liver disease and connective tissue diseases 13 .…”
mentioning
confidence: 99%